MANAJEMEN KEPALA SEKOLAH DALAM MENGHADAPI PERKEMBAGAN DI ERA REVOLUSI INDUSTRI 4.0 UNTUK MENINGKATKAN EFEKTIVITAS PROSES PENDIDIK PADA KURIKULUM MERDEKA BELAJAR - Putra, Dino Adi; Iskandar, M. Yakub; Efendi, Efendi; Sefrinal, Sefrinal; Amarullah, Taufik Abdul Hasan (STKIP Pesisir Selatan, 2025)
Various challenges, problems, and obstacles faced by the Principal in facing the Merdeka curriculum in the 4.0 era, This study uses a survey method conducted online. The sample of this study was 35 Principals from both public and private schools in the Pesisir Selatan area. The instrument used was a questionnaire distributed online using the ms.form link. The technique used to analyze the data was qualitative and quantitative descriptive analysis. The results of the study showed that the implementation of schools in facing the Merdeka curriculum was very effective when viewed from the readiness of the Principal. From the results of the study, the results were obtained through a series of six indicators and eleven statements, the average number of statements obtained was 90% stating that the principal could manage developments in the Industrial Revolution Era 4.0 in increasing the Effective Use of the Merdeka Curriculum and 10% Principals were not yet effective in implementing the Merdeka curriculum because the facilities and infrastructure were inadequate. If the learning system using the Merdeka Curriculum is implemented sustainably, the principal will be 100% ready effectively